Analisis lakuan komunikatif pemandu pelancong semasa bertugas (Jurnal Bahasa, 2005)
In the world of tourism, a multifaceted world that involves a variety of enterprises that offer different services to a variety of travellers, there exist a group of people who play a vital and indispensable role. This group of people, the tour guides, cater to the needs of travellers; tour-ists who travel to increase their knowledge of the world, to know more about other cultures, the country and its people. How does the tour guide disseminate the wealth of knowledge and rich culture of the coun-try to these people? How does he communicate with them? This research was carried out to investigate the "communicative acts" (Saville-Troike, 1989) employed by tour guides, a speech community in Malaysia. It is based on one "communicative situation" (Saville-Troike, 1989); the guided tours in and around Kuala Lumpur city and Malacca for foreign tourists. The research looked at one "communi-cative event" (Saville-Troike, 1989), i.e. tour guides communicating orally with their tourists while at work. In this paper, the findings will focus only on the communicative acts employed by the tour guides and the possible reasons for using these acts.